New data on the zooplankton of watercourses of the National Park "Krasnoyarsk Stolby" - Yermolaeva, Nadezhda; Fetter, Gleb; Zarubina, Eugenia; Tropina, Elena (Zenodo, 2023)
Based on natural materials collected by the authors in 2020-2022, data on zooplankton in the watercourses of the “Krasnoyarsk Stolby” National Park are summarized. A list of 85 species is given: 38 species and subspecies of rotifers, 26 species of cladocerans, 11 species of cyclops, and 10 species of harpacticidae. For the first time, 24 species of rotifers, 10 species of cladocerans, 14 species of copepods were discovered or identified to species. This study was carried out as part of State Task of Institute for Water and Environmental Problems Siberian Branch of the Russian Academy of Sciences (registration no. 0306-2021-0001) with the financial support of RUSAL Krasnoyarsk JSC (Agreement No. 29.03.02/2022 dated 01.03.2022).The authors express their sincere gratitude for the help in organizing the collection of material to the Deputy Director for Scientific Work of the National Park "Krasnoyarsk Stolby" A.A. Knorre. Special thanks to the staff of the territory protection department N.V. Vesnin, A.I. Petukhov, A.V. Pavlov for technical support and assistance in carrying out the work.